Self-Compassion to Improve Psychological Well-Being in Students: A Scoping Review - Ni Nyoman Armelia Dewi; Lailatul Badriah; Hilda Octri Nurahmah; Kartika Milaningrum (Indonesian Journal of Global Health Research, 2025)
Psychological well-being is important for students to have, but in reality, there are still students who don't have it. Optimal psychological well-being is expected to be able to encourage individuals to live a life of wellness, namely a state where a person is not only physically healthy but also has good mental health. A scoping review was conducted by searching literature in PubMed, ProQuest, Scopus, and Web of Science. Included studies (2020–2025) to discuss more deeply about self-compassion to improve psychological well-being in students, including effectiveness and strategies to improve psychological well-being in oneself, excluded were articles that are not full papers, duplicate articles, and articles that were withdrawn due to publication ethics. From this scoping review, of the 3.922 identified articles, seven studies met the criteria for further analysis. the results showed that self-compassion has an important role in improving students' mental, emotional and physical well-being through reducing symptoms of depression, anxiety and stress, as well as strengthening resilience, optimism and emotional regulation. The development of self-compassion is recommended as an effective approach to improve mental well-being and quality of life in various groups, including students and health professionals.